2015
DOI: 10.1371/journal.pone.0136185
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Both ERG11 and ABC2 Genes Might Be Responsible for Itraconazole Resistance in Clinical Isolates of Candida krusei

Abstract: ObjectiveTo study the main molecular mechanisms responsible for itraconazole resistance in clinical isolates of Candida krusei.MethodsThe 14α-demethylases encoded by ERG11 gene in the 16 C.krusei clinical isolates were amplified by polymerase chain reaction (PCR), and their nucleotide sequences were determined to detect point mutations. Meanwhile, ERG11 and efflux transporters (ABC1 and ABC2) genes were determined by quantitative real-time reverse transcription polymerase chain reaction (qRT-PCR) for their exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…Two strains from a hospital in Ireland form the closest pair in the tree (C-IE2, C-IE4) and group weakly with a third (C-IE1), but three other strains from the same hospital are scattered across the tree. All four clinical isolates from Tianjin, China [ 57 ] lie in Clade 2, and among these, two strains form a close pair (C-CN3, C-CN4) and are both triploid. The only sample from soil in our dataset, E-JP4, groups with samples from faeces (C-BR1) and sewage (E-JP1) to form Clade 1, indicating possible clustering by habitat.…”
Section: Resultsmentioning
confidence: 99%
“…Two strains from a hospital in Ireland form the closest pair in the tree (C-IE2, C-IE4) and group weakly with a third (C-IE1), but three other strains from the same hospital are scattered across the tree. All four clinical isolates from Tianjin, China [ 57 ] lie in Clade 2, and among these, two strains form a close pair (C-CN3, C-CN4) and are both triploid. The only sample from soil in our dataset, E-JP4, groups with samples from faeces (C-BR1) and sewage (E-JP1) to form Clade 1, indicating possible clustering by habitat.…”
Section: Resultsmentioning
confidence: 99%
“… He et al (2015) studied the molecular mechanisms responsible for itraconazole resistance in clinical isolates of C. krusei and found ERG11 gene polymorphisms that may not be involved in the development of itraconazole resistance in C. krusei , but overexpression of ERG11 and ABC2 might be responsible for the acquired itraconazole resistance of the clinical isolates.…”
Section: Discussionmentioning
confidence: 99%
“…For example, analysis of itraconazole-resistant C. krusei isolates revealed that reduced intracellular content of the drug and not altered affinity for the drug target likely drives itraconazole resistance (Marichal et al, 1995; Venkateswarlu et al, 1996). However, more recently it has been suggested that overexpression of genes encoding both Erg11p and the efflux pump Abc2p may also play a role with itraconazole resistance (Tavakoli et al, 2010; He et al, 2015). Despite its fungicidal activity in C. krusei (Rubio et al, 2005), resistance to voriconazole has also emerged, and current research supports a theory where overexpression of the genes encoding the efflux pump Abc2 and Erg11 impart more transient resistance properties, while increased expression of Abc1p and point mutations in ERG11 predominate as time progresses to yield a stably resistant pathogen in the prolonged presence of voriconazole (Ricardo et al, 2014).…”
Section: Azole Antifungal Resistance Mechanismsmentioning
confidence: 99%